'More constricting than inspiring' - GPs find chronic care programmes of limited clinical utility. A qualitative study. Issue 2 (2018) - Kristensen, Mads Aage Toft; Due, Tina Drud; Hølge-Hazelton, Bibi; Guassora, Ann Dorrit; Waldorff, Frans Boch
No abstract available